Distance Learning Programmes in Nigeria and the Question of Quality in Continuing Professional Development (CPD) - Maduako, Ibiere Ken (Richtmann Publishing, 2011)
Distance learning programmes are â€œalternative modelsâ€ of the teaching and learning situation where students carry outtheir studies remotely via the internet or videos, cassettes or webcastsâ€ in borrowed classrooms. The advantages of DLPsinclude: availability, self- directed, cheaper, little or no time spent in rigid classroom settings, accessibility, no travel expenses,and working at oneâ€™s convenience. These programmes can be quite exciting to those who can afford them in and out of tightschedules and they have become very popular in a modern and technological world such as ours. They afford working adultsopportunities to further their educational aspirations without leaving their jobs. The present paper tries to examine the strengthsand weaknesses of one of these programmes, the Continuing Professional Development (CPD) in Nigeria, in order to ascertainits quality and positive impact on the learners. Our major findings are that distance learning programmes are needful but thelaxities that come with them need to be checked for more qualitative student/ trainee output. The CPD in particular is aprogramme rich in content and purpose but its workability and modus operandi as designed by the British Council and TheNational Teachers Institute of Nigeria is not satisfactory. There is need for urgent reformations for the attainment of desiredresults in terms of quality.